Genome-wide association study revealed genomic regions related to white/red earlobe color trait in the Rhode Island Red chickens. Issue 1 (December 2016) - Nie, Changsheng; Zhang, Zebin; Zheng, Jiangxia; Sun, Hongyan; Ning, Zhonghua; Xu, Guiyun; Yang, Ning; Qu, Lujiang
Abstract Background Earlobe color is a naturally and artificially selected trait in chicken. As a head furnishing trait, it has been selected as a breed characteristic. Research has demonstrated that white/red earlobe color was related to at least three loci and sex-linked. However, there has been little work to date to identify the specific genomic regions and genes response to earlobe color in Rhode Island Red chickens. Currently, it is possible to identify the genomic regions responsible for white/red earlobe in Rhode Island Red chicken to eliminate this gap in knowledge by using genome-wide association (GWA) analysis. Results In the present study, genome-wide association (GWA) analysis was conducted to explore the candidate genomic regions response to chicken earlobe color phenotype. Hens with red dominant and white dominant earlobe was used for case-control analysis by Illumina 600 K SNP arrays. The GWA results showed that 2.38 Mb genomic region (50.13 to 52.51 Mb) with 282 SNPs on chromosome Z were significantly correlated to earlobe color, including sixteen known genes and seven anonymous genes. The sixteen genes werePAM, SLCO4C1, ST8SIA4, FAM174A, CHD1, RGMB, RIOK2, LIX1, LNPEP, SHB, RNF38, TRIM14, NANS, CLTA, GNE, andCPLX1 . Conclusions The study has revealed the white/red earlobe trait is polygenic and sex-linked in Rhode Island Red chickens. In the genome significant 2.38 Mb region, twenty-three genes were found and some of them could play critical roles in the formation of white/red earlobe color, especially geneSLCO4C1 . Taken together, the candidate genes findings herein can help elucidate the genomic architecture of response to white/red earlobe and provide a new insight on mechanisms underlying earlobe color in Rhode Island Red chickens and other breeds.